Risk Factors for Surgical Site Infections in Patients Operated at the University Clinic of Traumatology-Orthopedics and Restorative Surgery of the National Hospital and University Center Hubert Koutoukou Maga in Cotonou - DEGBEY, CYRIAQUE COMLAN; Makoutodé, Charles Patrick; AGUEMON, BADIROU DIN OWOLADÉ OTONIKOU (My University, 2023)
Background: Operative site infections (ISO) are typically nosocomial. According to the WHO the incidence of ISO varies from 0.5% to 15% and exceeds 25% in developing countries. They result from the combined action of several factors and represent a concern for public health. To study the contributing factors of surgical site infections in patients operated at the University Clinic of Orthopedic Traumatology of CNHU-HKM of Cotonou. Method: This was an analytical cross-sectional study that involved 35 operated patients and ten nurses. Were included in our study: 1) All patients, without distinction of sex or age, having been operated on in the university clinic of orthopedic traumatology, during the survey period; 2) Patients hospitalized for post-operative care during the survey period; 3) The nursing staff on duty during our study period. The usual statistical measures were used according to the type of variables: means, standard deviations, percentages. Data analysis first involved calculating percentages for the qualitative variables and means followed by their standard deviations for the quantitative variables. Next, the Pearson Chi-square test was used to test the association between the dependent variable and the independent variables of interest. The significance level is set at p < 0.05. Results: The prevalence of surgical site infections was 28.58%. The main factors contributing to the occurrence of SSIs that were found were the patient’s level of education (p = 0.003) and the reuse of ban-dages used for dressing (p = 0.004). Other potential factors such as the economic status of the patient, the poor quality of technical dressings, and the preoperative stay were also highlighted. Conclusion: Surgical site infections remain a global concern. Risk factors were found on both the patient and nurse sides. It is urgent to address these various factors to minimize the occurrence of surgical site infections
Keywords: Surgical Site Infection; Nosocomial Infections; Risk Factors; Patient; Benin